THE RIGHT TO KNOW ONE’S BIOLOGICAL IDENTITY - VERONICA DOBOZI (Challenges of the Knowledge Society)
In the last decade, European Court of Human Right case-law evolution revealed a new component of the right to private life, protected by the Human Rights Convention, Article 8. Existence and limits of the right to know one’s biological identity were set out in a long line of cases, starting with Mikulic c. Croatie (2002) until the very recent Godelli c. Italie (2012). The Court jurisprudence established that birth, and in particular the circumstances in which a child is born, forms part of a child’s, and subsequently the adult’s, private life guaranteed by Article 8 of the Convention. Respect for private life requires that everyone should be able to establish details of their identity as individual human beings and that an individual’s entitlement to such information is of importance because of its formative implications for his or her personality. This includes obtaining information necessary to discover the truth concerning important aspects of one’s personal identity, such as the identity of one’s parents. Having regard to the margin of appreciation left to the member states, the Court sticks between taking priority over the third parties’ right to privacy – for example, mothers in the cases of X births, donors sperm, unknown fathers – to recognition of the child’ right to know his/her biological roots and identity. Following the bioethics and bio-law progress, case-law evolution had influence member states legislation and disseminated progressive ideas, as the recent official United Kingdom legislative modifications which remove anonymity for sperm, egg and embryo donors. In view of the above, future analysis of private life respect throughout Europe should include this new element, the right of any person to know his/her biological identity, not only for medical aims.